Design and analysis of piezo actuated flexure guided nanopositioning stage. (2023) - Pankaj,; Chandra, Vikash; Murat, Ram; Kumar, Viresh
Abstract: Recent advancements and requirements in the field of high-speed scanning probe microscopy applications have sparked the attention of many researchers to develop highly precise flexure based nanopositioners. Major challenges faced by researchers while designing a piezo nanopositioning stage are the low range of motion, cross-coupling between the X and Y direction and low resonance leading to lower speeds. The finite element analysis study of the nano-positioning flexure stage stimulated with a piezo actuator has been presented in this research article to tackle these challenges. The design of the XY flexure stage is quite robust and incorporated with flexure hinges to transfer maximum deflection to the sample stage. The designed stage is capable of scanning a large range (85 × 85 µm) with a sub-nanometer resolution for high precision microscopy applications like atomic force microscope. The Finite Element Analysis (FEA) study using ANSYS software was successfully conducted to predict the resonance frequency of the mechanical structure and displacement that occurred at the sample platform due to the piezo actuator movement for different materials. The maximum displacement amplification factor for the designed mechanical stage was observed to be 4.280 for EN 47. The natural frequency of the stage varied from 1.366 kHz to 6.998 kHz predicted for the six modes of vibrations. The least displacement amplification factor and resonance frequency were determined for polylactic acid (PLA).